فكر ابن قيم الجوزية التربوي ومنهجه في الإسلام - محمود، ابراهيم خوجلي السيد (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
This study tries to investigate the views of Ibn Qayyim al-Jawziyyah on Islamic education and it's curriculum. By posing a number of specific questions the researcher assumed that the answers of these questions will guide us to the required results. The researcher used both descriptive analytical method and historical and philosophical method. The researcher employed deductive and inductive techniques. From the results of this investigation we can state that Ibn Qayyim al-Jawziyyah thinks that the main purpose of Islamic education and it's curriculum is to produce the ideal man, he maintained that man is the axis of the educational process. He stressed also that education should serve the purpose of vice-gerency. Hence, man is not created for trifle matters, he is responsible of his actions, and entrusted with the duty ofconstructing and developing earth. This can only be accomplished through an excellent educational curriculum. The highest aim of this curriculum shall be based on a clear world view of relationship between man and his universe, and between both the creator and the man and the universe. Ibn Qayyim al-Jawziyyah emphasized that the Islamic educational curriculum should involve essential human elements such as; the body, the soul, intellect and most importantly the creed (Aqeedah). The classification of the curriculum components which Ibn Qayyim visualised and divided into sciences as imposition, obligation, and the third as collective duty. He cleared out the philosophy of the curriculum, aims, contents, ways of implementation and measurement and evaluation all this represent firebrands of the educational thought of Ibn Qayyim and in the same time are the new and true supplementation of this study.